Ultra wide bandwidth indoor channel model based on measurements and physical approach. (18th February 2011) - Saadane, R.; Aboutajdine, D.
In this work, using a physic approach, which based on an analysis of physical propagation phenomenon like diffraction and reflection versus frequency band and the nature of material, we propose a new UWB channel statistical model. In particular we describe UWB channel delays and taps statistics. This analysis is done based on measurements campaign carried out at Eurecom Institute and provided over channel bandwidth from 3 to 9 GHz in different environments. Then we present a novel UWB channel model based on physical propagation effects and UWB channel measurements. A mathematical description of the model is discussed and the corresponding extraction parameter is p presented using a SAGE algorithm. Our proposed model gives a good fit to measurement data and it is easy to implement. Other features of this approach also are discussed.